Leaching and solution chemistry - Li, J.; McFarlane, A.; Klauber, Craig; Smith, P. (Cambridge University Press, 2017)
© Commonwealth Scientific and Industrial Research Organisation (CSIRO) 2017. Fundamental Dissolution Mechanisms of Clays The mechanisms of dissolution and precipitation at the mineral–water interface have been reasonably well understood in terms of natural mineral weathering and metal cycling processes (Aldushin et al., 2006; Hering and Stumm, 1990; Kalinowski and Schweda, 1996). The same mechanisms may be applicable to an understanding of mineral dissolution under hydrometallurgical conditions where non-equilibrium conditions with faster reaction kinetics prevail, due to higher lixiviant concentrations, temperature and pressure. Surface complexation models, within the framework of the transition state theory (TST) (Fig. 3.1) are often applied to explain the dissolution and precipitation of major rock-forming minerals in natural weathering processes (Schott et al., 2009 and references therein). The interaction between reactants A and B need to overcome an energy barrier (Ea) to form an activated complex species (AB‡) at the top of the barrier, which subsequently rearranges to yield products (C and D) at a lower final (Gibbs) free energy state. A simplified conceptual mineral dissolution model can be modified from that idea; the rate-determining step involves irreversible decomposition of the activated complex to form product species (Walther and Wood, 1986): Transition state theory treats the activated complex as a true chemical species. The surface chemistry concept of mineral dissolution developed suggests that oxides and oxide minerals in aqueous environments are covered with surface hydroxyl groups (S–OH) (Schindler and Stumm, 1987). Adsorption of H+and/or OH–ions causes protonation or deprotonation of the surface hydroxyl groups, forming a high-energy, activated complex or a combination of activated complexes: Proton adsorption to the mineral surface weakens the metal–oxygen bond, probably by depolarizing bonding electrons and therefore promoting the detachment of the metal ion from the bulk mineral (Cornell and Schwertmann, 2003). Adsorption of metal ions onto an oxide surface can be viewed as a competitive reaction involving one or more hydroxyl groups: Phyllosilicates can simply be viewed as consisting of various metal–oxygen bonds. The dissolution rate of any silicate mineral is primarily governed by the breakage of the slowest metal–oxygen bond essential for maintaining the given mineral structure. To understand the differences in metal–oxygen bonding strength, it is necessary to first explain the link between surface and aqueous chemistry (Schott et al., 2009).